Metods of digital filtration and their impacts on the quality of images of different classes - Yudin, О.; Veselska, O. (Science-based technologies, 2017)
Different methods of filtration and digital imaging classes have been analyzed and investigated. The frequency filtering method for digital imaging was implemented and the degree of distortion of the digital image was investigated; depending on the image class; separately for each component of the RGB color model. In the study of digital static images of different classes; methods of frequency filtration are used. The procedure for removing the segments of the spectrum of three color gamut is obtained. The indicated statistics may be the basis for further research for the development of modern effective methods of steganography and steganalization